2008
DOI: 10.1111/j.1708-8305.2008.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Imported Malaria to Basel, Switzerland: Table 1

Abstract: Prompt and specific diagnosis of malaria could be improved. Malaria-associated mortality was reduced over time. As ICU referral showed to be inappropriately high in relation to a moderate clinical course of several admitted patients, criteria for ICU admission should be reevaluated. The trend toward malaria in patients originating from endemic areas suggests that preventive travel advice should specifically address these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…In this series, only one death occurred at a time when there was evidence of active malarial infection and the other four resulted from complications associated with intensive care, such as cardiac arrhythmia or nosocomial infection. Previous studies have reported a mortality rate between seven and 25% [5-11]. Recent data from the Malaria Reference Laboratory have shown a marked geographical variation in mortality from imported malaria from different parts of the UK [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this series, only one death occurred at a time when there was evidence of active malarial infection and the other four resulted from complications associated with intensive care, such as cardiac arrhythmia or nosocomial infection. Previous studies have reported a mortality rate between seven and 25% [5-11]. Recent data from the Malaria Reference Laboratory have shown a marked geographical variation in mortality from imported malaria from different parts of the UK [23].…”
Section: Discussionmentioning
confidence: 99%
“…The case fatality rate for P . falciparum in the UK is less than 1% but in previous series the mortality rate for those patients requiring admission to an intensive care unit (ICU) as a result of malaria has varied from 7% to 25% [5-11]. Most data on severe malaria come from endemic countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature search identified 61 papers, 13 of which were included (Figure 1) [1,4-15]. Forty-eight were excluded; 22 were not published in English, 11 were not primary research articles, four reported only on paediatric cases and 11 were short case series that included fewer than ten patients.…”
Section: Resultsmentioning
confidence: 99%